Carte Polaire Sud, en projection stéréographique / Service hydrographique de la marine . 1956 (1966)
Publication Septembre 1956. Corr. . 1966 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings Color; 1:12,000,000